2012
DOI: 10.1103/physrevb.85.155411
|View full text |Cite
|
Sign up to set email alerts
|

Growth diagram and magnetic properties of hexagonal LuFe2O4thin films

Abstract: A growth diagram of Lu-Fe-O compounds on MgO (111) substrates using pulsed laser deposition is constructed based on extensive growth experiments. The LuFe 2 O 4 phase can only be grown in a small range of temperature and O 2 pressure conditions. An understanding of the growth mechanism of Lu-Fe-O compound films is offered in terms of the thermochemistry at the surface. Superparamagnetism is observed in the LuFe 2 O 4 film and is explained in terms of the effect of the impurity hexagonal LuFeO 3 (h-LuFeO 3 ) ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Supersaturation Δμ is the chemical potential difference of adatoms transitioning from their quasi‐vapor phase (the mobile adatoms on the surface and the background oxygen in the gas phase) near the substrate to their solid phase on the substrate. Below B3 the growth is non‐stoichiometric due to the inability of completing the thermo‐chemical transition from the quasi‐vapor phase to the solid phase of the intended compound 39. Above B3 the film can be grown with the right stoichiometry.…”
Section: Atomic‐level Control and Structure Of Surface Of Stronglymentioning
confidence: 99%
“…Supersaturation Δμ is the chemical potential difference of adatoms transitioning from their quasi‐vapor phase (the mobile adatoms on the surface and the background oxygen in the gas phase) near the substrate to their solid phase on the substrate. Below B3 the growth is non‐stoichiometric due to the inability of completing the thermo‐chemical transition from the quasi‐vapor phase to the solid phase of the intended compound 39. Above B3 the film can be grown with the right stoichiometry.…”
Section: Atomic‐level Control and Structure Of Surface Of Stronglymentioning
confidence: 99%
“…The ability to deposit single-crystal thin films of LuFe 2 O 4 is a key stepping stone on the path to understanding and manipulating the properties of this material, for example, with strain. 8,9 There has been some success with growing thin films of LuFe 2 O 4 by pulsed-laser deposition (PLD), [10][11][12] though so far this achievement is limited to polycrystalline films or films with impurity phases present, particularly at the interface. In these cases, the desired LuFe 2 O 4 phase only forms with excess iron present during growth by PLD.…”
mentioning
confidence: 99%
“…A good crystallographic orientation of f = 0.80 is achieved for the film heat treated at 900 • C. By the way, epitaxial RFe 2 O 4 films grown by MBE 7 and PLD 5,[8][9][10] techniques showed the perfect (001)-orientation. It is worth to mention that the highly (001)-orientation of spin coated films is nearly comparable to that of MBE and PLD films.…”
Section: Resultsmentioning
confidence: 80%
“…magnetic hysteresis because of the ferrimagnetic transition of YbFe 2 O 4 , although the observed M S of 22 emu/cm 3 is less than the reported bulk value of ∼80 emu/cm 3 at 20.5 kOe and 180 K. 15 A lower M S value in thin films than the bulk value has also be observed in LuFe 2 O 4 prepared by the MBE method. 7 The magnetic properties of RFe 2 O 4 are known to be sensitive to various factors, such as oxygen nonstoichiometry, 16 lattice strain, 17 impurities, 8 and the magnetic field experienced by the specimens. 18 From the presence of a clear ferrimagnetic transition in the magnetization curves, it can concluded that the YbFe 2 O 4 films prepared by spin coating have favorable crystalline properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation